Investigation of Small Hydropower Potential of River Oshin in Kwara State, North Central, Nigeria - Oladeji, A. S.; Akorede, M. F.; Mohammed, A. A.; Adeogun, A. G.; Salami, A. W. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This paper presents the investigation of hydropower potential of river Oshin via Babaloma in Ifelodun Local Government Area of Kwara State, North Central, Nigeria. The inhabitants of the study area which is a cluster of three off-grid rural communities: Sangotayo, Budo Umoru and Idi Isin lack access to electrical energy despite the huge potential for renewable energy resources most especially, the hydropower potential. Water velocity of the river was measured using Flow Probe FP211 model. The measured water velocity was converted to discharge using relationship between the channel geometry and velocity. Relationship between measured discharge and water level was used to develop rating equation for the river. Net head was estimated using Digital Elevation Model (DEM) embedded in ArcGIS (ArcMap 10.3) software. The results revealed that the average water level and discharge were high in the month of May through November with discharges varying between 3.48 to 11.90 m3/s while water levels ranged between 0.79 to 1.84 m. The relationship between the water level and discharge revealed a correlation coefficient of 0.99 with positive upward trend. The design flow of 4.63 m3/s was determined from the flow duration curve (FDC) while the net head was estimated as 7.62 m. The hydropower potential of the river at the sub-basin 9 was estimated as 363.36 kW which is in the range of mini hydropower plants (MHP). Annual energy generation from the river is estimated as 2624482.08kWh. The estimated hydropower potential can satisfy the present and future electricity needs of the inhabitants of the cluster of the three rural communities under consideration.